Redescription of Alpheus vladivostokiensis (Vinogradov, 1950), a large and conspicuous snapping shrimp from the northern Sea of Japan (Decapoda: Caridea: Alpheidae) - Anker, Arthur; Marin, Ivan N.; Pachelle, Paulo P.g.; Komai, Tomoyuki (Zootaxa, 2016)
The poorly described Alpheus vladivostokiensis (Vinogradov, 1950) comb. nov., originally assigned to the genus Betaeus Stimpson, 1860 and hitherto considered as a nomen dubium, is redescribed based on material recently collected in Troitza Bay in the Russian Far East and Hakodate Bay in southern Hokkaido, Japan, as well as older material deposited in the Zoological Museum of the Moscow State University. Since Vinogradov’s material is considered as non-extant, a neotype of A. vladivostokiensis is designated. Alpheus vladivostokiensis is closely related to A. japonicus Miers, 1879, a species occurring in deeper waters of Japan, Korea, China and Taiwan. All previous records of A. japonicus from the Russian Far East are reassigned to A. vladivostokiensis.